Treating Sudden Onset Hepatic Encephalopathy with Coil Embolization in a Patient with a Congenital Intrahepatic Portosystemic Venous Shunt: A Case Report - Jin Hyeok Kim; Ung Bae Jeon; Joo Yeon Jang; Tae Un Kim; Hwaseong Ryu (대한영상의학회지, 2022)
Intrahepatic portosystemic venous shunt (IPSVS) is a rare vascular abnormality that involves abnormal communication between the intrahepatic portal vein and systemic veins, such as the hepatic vein or inferior vena cava. Patients with IPSVS are typically asymptomatic, and IPSVS is incidentally discovered via imaging while evaluating other diseases. However, endovascular closure of the shunt should be considered in symptomatic patients with a high-flow shunt. This report presents a patient with congenital IPSVS with sudden onset hepatic encephalopathy treated using percutaneous transhepatic embolization.